Quality Research in Literacy and Science Education
XXIX, 666 p.
Keywords: This book addresses implications for "Gold Standards" of education research—especially in science education and literacy. These standards are meant to provide evidence-based educational outcomes found effective in randomized controlled trials, following patterns of evidence used in medical research. Similar expectations have emerged in other countries—from education ministries, for researchers working with U.S. colleagues, and for researchers with multinational and non-profit support. The current "Gold Standard" policy, developed in the United States through the 2001 "No Child Left Behind" [NCLB] Act and the 2002 Education Sciences Reform Act, attempts to improve the effects of schooling and enhance educational research. The contributions to this book explore perspectives on how best to implement multiple standards of education research.